Search for the doubly charmed baryon Ξ+ccΞcc+ in the Ξ+cπ−π+Ξc+π−π+ final state; Journal of High Energy Physics; Vol. 2021, iss. 12 - Aaij R. Roel; Abdelmotteleb A. S.; Beteta C. A. Carlos Abellan; Panshin G. L. Gennady Leonidovich; Kharisova A. E. Anastasiya Evgenjevna (2021, 2021)
Title screen